ANALISIS PEMOTONGAN PPH PASAL 4 AYAT 2 TERHADAP LELANG PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG MANADO - Djohar, Angreani A.; Karamoy, Herman; Warongan, Jessy D.L (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Income tax article 4 (2) is the final income tax that is the collection institutions is central government. The auction is a kind of income subject to income tax article 4 (2). The auction tax rate of 2,5% on PP RI No. 34 year 2016. Service office a wealth of state and of government agencies is Manado auction that runs the basic tasks in the field of auctions. The methods used in this research is descriptive research method is qualitative. As for the purpose of this research is to analyze system cutting the income tax article 4 (2) on auction at the service office a wealth of state and the auction Manado. Based on research results from service office a wealth of state and the auction Manado cutting of the income tax article 4 (2) is in compliance to applicable government regulations. Service office a wealth of state and the auction Manado are expected to carry out the duty taxes according government regulation and improve understanding and active in the running of government regulation.Keywords : Income Tax Article 4 (2), Cutting, Auction